THE EFFECT OF SILICA AND MANGANESE APLICATION ON RICE GROWTH AND YIELD - Timotiwu, Paul Benyamin; Dewi, Maya Maeistia (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
The increasing demand of rice each year as the consequences of population growth increases rice production in Indonesia.Â The increasing of growth and yield of rice can be achieved through micro elementapplication. Â The application of silica and manganese through the leaves can be directly absorbed by the rice plants for growth and photosynthetic process.Â It is beneficial to produce a higher rice yield. Â This study aimed to determine the effect of the increasing of silica and manganese concentration, and their interaction on plant growth and yield of rice.Â The green house research was conducted in the Seed and Plant Breeding Laboratory, Faculty of Agriculture, University of Lampung, JuneâSeptember 2013.Â The treatments were arranged in a 5x2 factorial [five concentrations of Si (0, 50, 100, 150, and 200 ppm), with and without (5ppm) of Mn] in a randomized complete block design (RCBD) with three replication.Â Orthogonal contrast and polynomial analyses were used to find the effect of Mn, Si, and their interaction. Â The results showed that increasing concentration of Si increased the greenness of leaves, number of productive tillers, weight of dry matter, number of filled grains, and decreased angle of the tiller and number of empty grains. Â The application of Mn increased the growth and yield of rice, angle of tiller and number of empty grains. Â In addition the effect of Mn was depended on the level of Si concentration.Â Application of Mn with increasing Si concentration increased of plant growth and yield of rice.Key words:Â rice, silica, manganese